Automated identification and measurement of Hematopoietic Stem Cells in 3D Intravital Microscopy Data - Khorshed,RA; Lo,Celso C (InTech, 2016)
Image analysis and quantification of Haematopoietic stem cells (HSCs) position within their surrounding microenvironment in the bone marrow is a fast growing area of research, as it holds the key to understanding the dynamics of HSC-niche interactions and their multiple implications in normal tissue development and in response to various stress events. However, this area of research is very challenging due to the complex cellular structure of such images. Therefore, automated image analysis tools are required to simplify the biological interpretation of 3D HSC microenvironment images. In this chapter, we describe how 3D intravital microscopy data can be visualised and analysed using a computational method that allows the automated quantification of HSC position relative to surrounding niche components.